Recapping actions, knowledge, and use of safety boxes with the incident of needle stick injuries in nurses at the inpatient installation of the Gadjah Mada University Academic Hospital, Yogyakarta - Ramsi, Rahmat Muzakky; Surono, Agus; Sutena, Marthinus (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to determine the relationship between recapping actions, knowledge, and use of safety boxes with needle stick injuries (NSI) and controlling the risk of NSI among nurses at the UGM Academic Hospital inpatient installation. Methods: Mixed methods with a cross-sectional design and analyzed descriptively, then conducted interviews to control risk. Sampling was performed using the proportional random sampling technique, involving 80 nurses and five informants from hospital management. Results: Recapping (p=0.041) and knowledge (p=0.005) had a significant effect on the incidence of needle stick injuries among nurses at the RSA UGM inpatient installation (90% CI, 0.12-0.79). The act of recapping has a 0.35 times smaller chance of getting NSI. Furthermore, nurses who have high knowledge have a 0.2 times lower risk of getting NSI. Meanwhile, the use of a safety box did not affect NSI (p=0.246). Conclusion: Recapping actions and knowledge are factors that influence NSI among nurses at the RSA UGM inpatient installation. Risk control that is already running well needs to be improved, such as adding material variations, sharing, comprehensive and practical educational methods for nurses.